Anxiety and depression in the Republic of Ireland during the COVID‐19 pandemic. (9th August 2020) - Hyland, P.; Shevlin, M.; McBride, O.; Murphy, J.; Karatzias, T.; Bentall, R. P.; Martinez, A.; Vallières, F.
Abstract : Background: The COVID‐19 pandemic in Ireland resulted in a nationwide quarantine on March 27, 2020. This study represents the first assessment of rates of anxiety and depression in the general population of Ireland during the pandemic. Aims: Our first aim was to estimate the probable prevalence rates of generalized anxiety disorder (GAD) and depression and to identify sociodemographic risk factors associated with screening positive for GAD or depression. Our second aim was to determine if COVID‐19 related anxiety was highest amongst those in society at greatest risk of morality from COVID‐19. Method: Self‐report data were collected from a nationally representative Irish sample ( N  = 1041) online between March 31 and April 5; the first week of the nationwide quarantine measures. Recognized cut‐off scores on the GAD‐7 and PHQ‐9 were used to estimate rates of GAD and depression. Correlates of screening positive for GAD or depression were assessed using logistic regression analysis. Results: GAD (20.0%), depression (22.8%) and GAD or depression (27.7%) was common. Screening positive for GAD or depression was associated with younger age, female sex, loss of income due to COVID‐19, COVID‐19 infection and higher perceived risk of COVID‐19 infection. Citizens aged 65 and older had significantly higher levels of COVID‐19 related anxiety than adults aged 18–34. Conclusions: Initial results from this multi‐wave study monitoring changes in population anxiety and depression throughout the pandemic indicate that GAD and depression were common experiences in the population during the initial phase of the COVID‐19 pandemic.